DETECTION OF INDEL-MARKERS IN GENOMES OF BURKHOLDERIA PSEUDOMALLEI STRAINS FOR INTRA-SPECIES GENOTYPING - M. L. Ledeneva (Журнал микробиологии, эпидемиологии и иммунобиологии, 2017)
Aim. Search for potential INDEL-markers in genomes of Burkholderia pseudomallei strains, as well as evaluation of the possibility of their use for intra-species genotyping. Materials and methods. Full-genome sequences of 25 В. pseudomallei strains with known geographic regions of isolation from GenBank database were studied. INDEL-marker search was carried out using authors’ program Gene Expert. Cluster analysis was carried out using genetic distance by R. Sokal and C. Michener and neighbor joining method. Results. 11 INDEL-markers were detected that allowed to split the studied strains into 13 genotypes. Spectrum of INDEL-patterns characteristic for Australian strains was determined. A possibility of existence of certain phylogeographic patterns of Thailand isolates is shown. Conclusion. A possibility of INDEL-markers to differentiate isolates of B. pseudomallei into 2 geographic populations (Australian and South-eastern Asia origin) that allows to determine the source of melioidosis outbreak and transmission routes of the pathogen is detected.